Upaya Muhammadiyah Menggali Potensi Pemulung TPST Piyungan Melalui Pemberdayaan Masyarakat: Muhammadiyah's Efforts to Explore the Potential of Piyungan TPST Scavengers Through Community Empowerment - Farid, Muhammad Rifa'at Adiakarti; Priyono Putra, Verryanto Eko; Adriyani, Lies Wuryanita; Rahman, Nuril Endi (Journal of Community Development and Disaster Management, 2024)
This research discusses Muhammadiyah's efforts regarding the scavenger empowerment program at the Piyungan TPST. The objectives of this research are (1) To find out the problems faced by the Community Empowerment Council (MPM) in carrying out community empowerment programs at Piyungan TPST. (2) Knowing the impact of the community empowerment program carried out by MPM at Piyungan TPST. This research uses descriptive qualitative methods. The results of the research show (1) The problems faced by MPM originate from the surrounding community who do not know the empowerment program in detail. (2) The impact that occurs in the community is to unite in one community which was previously scattered into several groups of collectors and better understand their own potential through empowerment activities